Turbulent-Prandtl-number models for liquid lead-bismuth in triangular rod bundles - LIU Shuyong; YU Dali; MEI Huaping; WANG Zhen; ZHANG Shichao; LI Taosheng (He jishu, 2022)
BackgroundIn order to accurately predict the heat transfer characteristics in the sub-channel of fuel assembly for the low Prandtl number fluid, it is necessary to select a suitable turbulent-Prandtl-number model.PurposeThis study aims at the applicability of turbulent-Prandtl-number models for liquid lead-bismuth turbulence in triangular fuel rod bundles.MethodsBased on the triangular rod bundle heat transfer correlation, the turbulent models of Shear Stress Transfer (SST) k-ω was adopted to analyze the different rod bundle structures for five different kinds of turbulent-Prandtl-number models. The analysis results were compared with the recommended heat transfer correlation, which had been verified by experiment in the sub-channels for liquid lead-bismuth. The applicability of various turbulent-Prandtl-number models under different rod diameters and pitch diameter ratios was analyzed in details.ResultsThe results show that the global turbulent-Prandtl-number model is not only related to the Reynolds number Re and Peclet number Pe, but also related to the pitch-to-diameter ratio (P/D). In the entire region of (1.3≤P/D≤1.7), simulation results of turbulent-Prandtl-number model proposed by Kays are in good agreement with the values calculated by Mikityuk equation. All sorts of turbulent-Prandtl-number models have the best P/D scope of application.ConclusionsThe related turbulent-Prandtl-number models can be used to predict the heat transfer characteristics of liquid lead-bismuth in the triangular rod bundles under different pitch diameter ratios.